P-031 AN UNUSUAL CASE OF AN INCARCERATED 5MM PORT SITE HERNIA FOLLOWING LAPAROSCOPIC FUNDOPLICATION. (13th October 2022) - Christopoulos, P; Sinha, S; Browning, M; Bradley, A; Andrews, S
Abstract: Aim: Port site hernias are a rare, but recognised risk of laparoscopic surgery. Literature supports fascial closure at port sites of 10mm or greater. However, there are few reported cases of herniation through 5mm port sites. Methods: This case report focuses on a 67-year-old female who underwent an uncomplicated primary laparoscopic Toupet's fundoplication. 11 days post procedure she presented with an incarcerated port site hernia. CT scan demonstrated high grade small bowel obstruction with a transition point at the site of the 5mm right sided port. A laparotomy was performed, the hernia reduced, small bowel was viable, and the port site hernia was closed internally using vicryl sutures. Results: The incidence of 5mm trocar-site hernias is rare. A recent literature review found only 10 such cases related to general surgery (cholecystectomy:6; appendicectomy: 2; right hemicolectomy: 1; paraesophageal hernia:1). Risk factors for port-site hernias include: high BMI, midline position, size, number and type of trocar tip. The limited current literature identifies excessive trocar manipulation as the major risk factor for developing 5mm port-site hernias, yet routine fascial closure is not supported. Conclusion: Herniation at 5mm port sites is rare but attention should be paid when patients present with symptoms suggesting its occurrence.